2010
DOI: 10.1080/00207144.2011.522914
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Responsiveness:Expectancy, Attitudes, Fantasy Proneness, Absorption, and Gender

Abstract: This study examines the effect of providing information linking participants' attitudes toward hypnosis with later hypnotic performance. Using total scale scores from McConkey's Opinions About Hypnosis scale, as well as subscale scores, the authors found a weak association between attitudes and performance among 460 student participants; however, the correlation was unaffected by prehypnotic information specifically connecting attitudes and performance. A brief, 3-item measure of hypnotic expectancies generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 24 publications
(34 reference statements)
1
26
0
2
Order By: Relevance
“…However, the existence of multiple subtypes of highs and lows (Balthazard and Woody, 1989; Pekala and Forbes, 1997; Green and Lynn, 2011; Terhune et al, 2011) suggests that it is unlikely that one biological determinant may account for such a complex trait like the susceptibility to hypnosis, and we may expect that several neurotransmitters and neuromodulators influence hypnotizability (Ott et al, 2005; Klinkenberg et al, 2011). Recent evidence suggests a role for nitric oxide (NO) because the hypnotizability-related vascular responses to cognitive and physical stimulation indicate greater NO availability in the highs’ vessels (Jambrik et al, 2004; Jambrik et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the existence of multiple subtypes of highs and lows (Balthazard and Woody, 1989; Pekala and Forbes, 1997; Green and Lynn, 2011; Terhune et al, 2011) suggests that it is unlikely that one biological determinant may account for such a complex trait like the susceptibility to hypnosis, and we may expect that several neurotransmitters and neuromodulators influence hypnotizability (Ott et al, 2005; Klinkenberg et al, 2011). Recent evidence suggests a role for nitric oxide (NO) because the hypnotizability-related vascular responses to cognitive and physical stimulation indicate greater NO availability in the highs’ vessels (Jambrik et al, 2004; Jambrik et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ezek alapján kijelenthetjük, hogy a hipnábilitás stabil személyiségvonás. A hipnotikus kapacitás magasabb szintje kapcsolatban áll az abszorpcióra (bevonódásra) való képességgel és a képzelet intenzív mûködésével (Green & Lynn, 2011), sôt egyes teoretikusok szerint a hipnábilitás egyenesen az imaginatív bevonódás függvénye (Hilgard, 1979), amit az eltérô hipnábilitású személyek éber állapotban történô elektrofiziológiai vizsgálata is megerôsített (pl. De Pascalis, 1993).…”
Section: Bevezetésunclassified
“…Bizonyos szülôi nevelési stílusok is kapcsolatban álltak a felnôttkori hipnábi-litással. Késôbbi, kvantitatív technikákat alkalmazó kutatások ugyancsak igazolták a fantáziakészség és a hipnábilitás kapcsolatát (Green & Lynn, 2011). Hipnózis hatására esetenként még a gyengén hipnábilis személyek képzeleti tevékenysége is felerôsödik.…”
Section: Képzeleti Bevonódásunclassified
“…He reported no correlations between scores on the OAH and the HGSHS:A (r = .05), as was the result for McConkey's study. However, more recently, Green and Lynn (2011) found that the total OAH score and one of its subscales correlated significantly with total HGSHS:A score (r = .22 and r = .23, respectively): This subscale was "automaticity/dissociation," which suggests that responsiveness is automatic, involuntary, and that participants are not aware of anything other than suggested events. The author reported a weak relation between perceptions of hypnosis as an altered state and subsequent responsiveness to hypnotic suggestions.…”
mentioning
confidence: 94%